Confirmation of validity of the developed translational model of chronic heart failure in rats - I. B. Tsorin; V. V. Barchukov; E. O. Ionova; V. N. Stolayruk; M. B. Vititnova; S. A. Kryzhanovskii (LLC "Publisher OKI", 2020)
The exprimants based on our translational model of chronic post-infarction heart failure within the use of echocardiography showed that in animals after 90 days after the reproduction of the myocardial infarction compared to the sham operated animals there is a significant increase in the endsystolic and end-diastolic sizes of the left ventricle (respectively, from 2.49 ± 0.09 to 3.91 ± 0.17 mm, p = 0.0002, and from 3.56 ± 0.12 to 5.20 ± 0.19 mm, p = 0.0002) and the decrease of its inotropic function that indicates a simulated pathology. 5 days after the echocardiographic study, the animals' exercise tolerance was assessed in the treadmill-run to failure test. It is proved in rats that 90 days after the coronary artery litigation the tolerance of physical activity decreases sharply - the value of the distance covered by them is 109.21 ± 11.61 m, which is 2.5 times less than the distance covered by sham operated animals (p = 0.003) and 5.3 times less than the distance covered by intact rats (p = 0.0001), - which is pathognomonic for chronic heart failure and complements the data of previously conducted morpho-histological, biochemical and molecular studies, indicating that the present model reproduces the main clinical and diagnostic signs of the simulated pathology.